A network meta-analysis of the relative efficacy of treatments for actinic keratosis of the face or scalp in Europe. - Stefan Vegter; Keith Tolley (PLoS ONE)
Background Several treatments are available for actinic keratosis (AK) on the face and scalp. Most treatment modalities were compared to placebo and therefore little is known on their relative efficacy. Objectives To compare the different treatments for mild to moderate AK on the face and scalp available in clinical practice in Europe. Methods A network meta-analysis (NMA) was performed on the outcome "complete patient clearance". Ten treatment modalities were included: two 5-aminolaevulinic acid photodynamic therapies (ALA-PDT), applied as gel (BF-200 ALA) or patch; methyl-aminolevulinate photodynamic therapy (MAL-PDT); three modalities with imiquimod (IMI), applied as a 4-week or 16-week course with 5% imiquimod, or a 2-3 week course with 3.75% imiquimod; cryotherapy; diclofenac 3% in 2.5% hyaluronic acid; 0.5% 5-fluorouracil (5-FU); and ingenol mebutate (IMB). The only data available for 5% 5-FU was from one small study and was determined to be too limited to be reliably included in the analysis. For BF-200 ALA and MAL-PDT, data from illumination with narrow-band lights were selected as these are typically used in clinical practice. The NMA was performed with a random-effects Bayesian model. Results 25 trials on 5,562 patients were included in the NMA. All active treatments were significantly better than placebo. BF-200 ALA showed the highest efficacy compared to placebo to achieve total patient clearance. BF-200 ALA had the highest probability to be the best treatment and the highest SUCRA score (64.8% and 92.1%), followed by IMI 5% 4 weeks (10.1% and 74.2%) and 5-FU 0.5% (7.2% and 66.8%). Conclusions This NMA showed that BF-200 ALA, using narrow-band lights, was the most efficacious treatment for mild to moderate AK on the face and scalp. This analysis is relevant for clinical decision making and health technology assessment, assisting the improved management of AK.